A Fresh Look at the Health-Wealth Correlation: A Case Study of European Countries - Teresa García-Mu\~noz; Shoshana Neuman; Tzahi Neuman (Institute of Labor Economics (IZA), 2019)
This paper contributes to the development-health literature by studying the correlation between development measures (see below) and health measures - one subjective ('self-assessed-health-status'), and the other one objective (the individual's 'number of chronic diseases'). Correlations are examined for 29 European countries, using the SHARE data set, and country-level development measures. Specifically, we examine whether country fixed-effects in regressions of health measures, controlling for individual socio-demographic variables, are significantly correlated with country development variables, which include: logarithm of per-capita GDP; the Human Development Index; the Social Progress Index; life expectancy; percentage of GDP spent on health; and the novel measure expressed by the Environmental Health Index. The novelty of our study is the introduction of a channel for the significant health-wealth correlation, speculating that the driving forces are psychological.
Keywords: I1; I15; 330; development; self-assessed-health-status; diseases; environmental hazards; psychological motives; SHARE; Europe